(untitled) (Indian Journal of Animal Production and Management, 2024)
Comparative feed intake and nutrient utilization were studied in adult bucks of Sirohi, Marwari and Kutchi breeds. The bucks were provided Cajanus cajan straw ad libitum as basal roughage, concentrate mixture 400 g/buck/day and green grass (Cenchrus ciliaris) one kg /buck/day as a supplement. The intake of DM, OM and CP were significantly less in Marwari bucks, whereas these values were similar between Sirohi and Kutchi. Total water intake /kg DM intake was similar in all the three breeds. Significantly (p<0.05) less water loss through faeces was observed in Marwari than Kutchi and Sirohi. The digestibility coefficient of different feed nutrients did not differ significantly among the breeds. However, Marwari bucks performed better in term of nutrients digestibility as compared to Sirohi and Kutchi. Despite wide variation in the morphological characteristics, negligible variation in voluntary feed intake and nutrient utilization were observed between the breeds, which confirm that all the three breeds were well adapted to the intensive system of feeding and management.